Genome-wide analysis of the carotenoid cleavage dioxygenases gene family in Forsythia suspensa: Expression profile and cold and drought stress responses - Zhao, Xiao-Liang; Yang, Ya-Lin; Xia, He-Xiao; Li, Yong (Frontiers in Plant Science, 2022)
Forsythia suspensa is a famous ornamental and medicinal plant in Oleaceae. CCD family is involved in the synthesis of pigments, volatiles, strigolactones, and abscisic acid (ABA) in plants. In this study, the CCD family in F. suspensa was analyzed at the genome level. A total of 16 members of the CCD family were identified, which included 11 members of the carotenoid cleavage dioxygenases (CCD) subfamily and 5 members of the 9-cis epoxycarotenoid dioxygenases (NCED) subfamily. The expression analysis of different tissues demonstrated that three FsCCD1 genes might be involved in the synthesis of pigments and volatiles in flowers and fruits. Three CCD4 genes were effectively expressed in flowers, while only FsCCD4-3 was effectively expressed in fruits. Comparison of CCD4 between Osmanthus fragrans and F. suspensa showed that the structure of FsCCD4-1 is was comparable that of OfCCD4-1 protein, indicating that the protein might be performing, especially in catalyzing the synthesis of β-ionone. However, further comparison of the upstream promoter regions showed that the proteins have major differences in the composition of cis-elements, which might be responsible for differences in β-ionone content. On the other hand, four NCED genes were significantly up-regulated under cold stress while two were up-regulated in drought stress. The data showed that these genes might be involved in the synthesis of ABA. Taken together, our data improves understanding of the CCD family and provides key candidate genes associated with cold and drought stresses in F. suspensa.